The Relationship Between Emotional Intelligence And Student Achievement In Social Studies Subject Class IX SMP Negeri 10 Samarinda Academic Year 2021/2022 - Wahyuni Wahyuni; Nasib Subagio; Sutrisno Sutrisno (Educational Studies: Conference Series, 2021)
The purpose of this study was to determine the level of emotional intelligence and the level of student achievement, as well as to determine whether there is a significant relationship between emotional intelligence and student achievement in social studies subject class IX SMP Negeri 10 Samarinda in the academic year 2021/2022. Sampling in this study used a probability sampling technique with proportional random, namely 78 students from 326 students of class IX SMP Negeri 10 Samarinda. The type of research used is quantitative research with a correlational approach. In an effort to collect data (research instruments), the author uses a Likert scale, namely the emotional intelligence scale which refers to the 5 (five) elements of emotional intelligence and documentation of student report cards to determine the value of learning achievement. Testing the validity of items and elements on the emotional intelligence scale was carried out by expert validation. To find the correlation between the two research variables, Pearson's Poduct Moment correlation was used and the analysis used the computer-assisted SPSS 23 for Windows program. Based on the results of the study, it showed that there was a significant relationship between emotional intelligence and student achievement in class IX of SMP Negeri 10 Samarinda. From the results of the calculation analysis, the value of sig = 0.000 and rcount = 0.407 means that the value of sig 0.000 < 0.05 and rcount is consulted with the rtable of product moment known to be at a significant level of 5% = 0.222, which means the value of rcount = 0.407 > rtable = 0.222. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.